2022
DOI: 10.18632/aging.204270
|View full text |Cite
|
Sign up to set email alerts
|

The downregulated drug-metabolism related ALDH6A1 serves as predictor for prognosis and therapeutic immune response in gastric cancer

Abstract: Drug metabolism-associated genes have been clarified to play a vital role in the process of cancer cell growth and migration. Nevertheless, the correlation between drug metabolism-associated genes and gastric cancer (GC) has not been fully explored and clarified. This paper has focused on the role of aldehyde dehydrogenase 6 family member A1 (ALDH6A1), a drug metabolism-associated gene, in the immune regulation and prognosis of GC patients. Using several bioinformatics platforms and immunohistochemistry (IHC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…As we expected, the A549 cells that with overexpressed long‐lived mammals ALDH6A1 showed inhibited migration compared to A549 cells transfected with the PEGFP control and mouse ALDH6A1 (Figure 4d,e , Figure S10b ). This not only evidenced that ALDH6A1 overexpression could inhibit growth and migration of cancer cells (Cai et al, 2022 ), but also indicated the ALDH6A1 of long‐lived mammals show stronger inhibition of cellular migration of cancer cells. However, there are some subtle differences in migration ability among cells expressed four long‐lived mammals ALDH6A1 .…”
Section: Resultsmentioning
confidence: 77%
“…As we expected, the A549 cells that with overexpressed long‐lived mammals ALDH6A1 showed inhibited migration compared to A549 cells transfected with the PEGFP control and mouse ALDH6A1 (Figure 4d,e , Figure S10b ). This not only evidenced that ALDH6A1 overexpression could inhibit growth and migration of cancer cells (Cai et al, 2022 ), but also indicated the ALDH6A1 of long‐lived mammals show stronger inhibition of cellular migration of cancer cells. However, there are some subtle differences in migration ability among cells expressed four long‐lived mammals ALDH6A1 .…”
Section: Resultsmentioning
confidence: 77%
“…Gastric cancer originates from the epithelial cells of the gastric mucosa, and it poses a significant health challenge due to its aggressive nature, propensity for invading adjacent organs, such as the esophagus, pancreas, and liver, and high incidence of lymph node and distant metastasis [ 16 , 17 ]. Moreover, gastric cancer is the second-most common malignant tumor in China, and it constitutes approximately half of the global number of gastric cancer cases, with an upward trend [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…GO/GSEA enrichment and single-cell data analysis illustrate an association between EDA and immune related pathway, especially interferon-gamma response. Besides perioperative chemotherapy, immunotherapy has been illustrated to have an important effect from third-line treatment to first-line treatment in GC patients [ 30 ]. We revealed that expression of EDA was negatively related to indicated immune checkpoints, suggesting that EDA may be a new biomarker or target for immunotherapy focusing on its effect on cancer-associated fibroblasts.…”
Section: Discussionmentioning
confidence: 99%